Genomic profiling of thousands of candidate polymorphisms predicts risk of relapse in 778 Danish and German childhood acute lymphoblastic leukemia patients - Wesołowska, Agata; Borst, L.; Dalgaard, M. D.; Yadav, R.; Rasmussen, K. K.; Wehner, P. S.; Rasmussen, M.; Ørntoft, T. F.; Nordentoft, I.; Köhler, Rolf; Bartram, Claus R.; Schrappe, M.; et al. (Leukemia, 2015)
Childhood acute lymphoblastic leukemia survival approaches 90%. New strategies are needed to identify the 10-15% who evade cure. We applied targeted, sequencing-based genotyping of 25 000 to 34 000 preselected potentially clinically relevant single-nucleotide polymorphisms (SNPs) to identify host genome profiles associated with relapse risk in 352 patients from the Nordic ALL92/2000 protocols and 426 patients from the German Berlin-Frankfurt-Munster (BFM) ALL2000 protocol. Patients were enrolled between 1992 and 2008 (median follow-up: 7.6 years). Eleven cross-validated SNPs were significantly associated with risk of relapse across protocols. SNP and biologic pathway level analyses associated relapse risk with leukemia aggressiveness, glucocorticosteroid pharmacology/response and drug transport/metabolism pathways. Classification and regression tree analysis identified three distinct risk groups defined by end of induction residual leukemia, white blood cell count and variants in myeloperoxidase (MPO), estrogen receptor 1 (ESR1), lamin B1 (LMNB1) and matrix metalloproteinase-7 (MMP7) genes, ATP-binding cassette transporters and glucocorticosteroid transcription regulation pathways. Relapse rates ranged from 4% (95% confidence interval (CI): 1.6-6.3%) for the best group (72% of patients) to 76% (95% CI: 41-90%) for the worst group (5% of patients, P<0.001). Validation of these findings and similar approaches to identify SNPs associated with toxicities may allow future individualized relapse and toxicity risk-based treatments adaptation.
advance online publication, 25 July 2014
Gesehen am 30.06.2020